Determination of Deoxygenation Coefficient for Al-Robat and Al-Jubyla Creeks in Basrah City/ South of Iraq - Hadi, Hanaa A.; Khudhair, Kifah M. (Basrah Journal for Engineering Sciences, 2021)
Al-Robat and Al-Jubyla creeks, which composes the study area, are two of the main six creeks branched from Shatt Al- Arab river in Basrah province, south of Iraq. They are used as open drains for discharging untreated sanitary sewage which caused the depletion of their dissolved oxygen and subsequently the deterioration of their water quality. To study the impact of discharging untreated sanitary sewage on study area water quality, measured in terms of dissolved oxygen concentration, it is necessary to determine the values of deoxygenation coefficient ( K 1 ). The aim of this study is to find K 1 values for the study area using laboratory results of BOD time series analyses. For this purpose, water samples were collected from eight locations distributed along the study area. Thomas graphical method was applied to calculate K 1 . The results showed that the K 1 values for Al-Robat and Al-Jubyla creeks ranged from 0.279 to 0.488 day ˗ 1 at 20 °C with ultimate BOD values varied over the range (40.5-258.6) mg/l. These results revealed that the water in Al-Robat and Al-Jubyla creeks has the characteristics of raw sewage.